Urban Sufism and Socio-Religious Transformation: A Study of the Qadiriyah Naqshbandiyah Order - Saudah Al-Amilatul Khalishah Afifi; Sulanam Sulanam; Mustaniroh Mustaniroh; Muhammad Ufuqul Mubin; Tri Pujiati; Imamuddin Imamuddin (UAS PRESS, 2026)
This study addresses a gap in existing scholarship on Sufi orders, which has largely focused on individual spiritual experience while paying limited attention to socio-religious transformation within urban religious communities. It examines how members of the Qadiriyah Naqshbandiyah Order (TQN) at PP Sabilul Muttaqin in Mojokerto City construct religious meaning and experience socio-religious transformation in an urban context. Using a qualitative approach with an interpretative phenomenological design, the study involved disciples, pesantren administrators, and key religious figures, including the mursyid and khalifah. Data were collected through in-depth interviews, participant observation, and document analysis, then analyzed using Interpretative Phenomenological Analysis (IPA) supported by social construction and social change perspectives. The findings demonstrate that the urban tarekat community functions not only as a space for spiritual practice, but also as a socio-religious institution that shapes collective behavior and social engagement. Religious rituals and guidance within the tarekat encourage stronger religious discipline, self-control, solidarity, and active participation in community life. In the urban setting of Mojokerto City, the tarekat also provides members with moral orientation and social stability amid the challenges of modern urban life. The study highlights the novelty of understanding urban tarekat communities as agents of socio-religious transformation that integrate spirituality with everyday social practices. It further suggests the need for comparative and longitudinal studies on the sustainability of tarekat-based transformation in contemporary urban societies.